2021
DOI: 10.1002/ab.21998
|View full text |Cite
|
Sign up to set email alerts
|

Effects of violent and nonviolent sexualized media on aggression‐related thoughts, feelings, attitudes, and behaviors: A meta‐analytic review

Abstract: Women are often depicted as sex objects rather than as human beings in the media (e.g., magazines, television programs, films, and video games). Theoretically, media depictions of females as sex objects could lead to negative attitudes and even aggressive behavior toward them in the real world. Using the General Aggression Model (Anderson & Bushman, 2002) as a theoretical framework, this meta-analytic review synthesizes the literature on the effects of sexualized media (both violent and nonviolent) on aggressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 82 publications
0
9
1
Order By: Relevance
“…Regardless of how the data were analyzed, the use of pornographic magazines was correlated with self-reported sexual aggression, and stronger linear associations were evident among men with higher predisposed risk of sexual aggression, especially with respect to HM. The total variance in self-reported sexual aggression accounted for by pornographic magazine use was moderate (9-17% in multiple regression analysis; IRRs ranged from 1.31 -1.86) and with respect to the multiple regression results, considerably larger than the reported estimate from a recent meta-analysis concerning "sexualized media" (Burnay et al, 2021). It possible that the analytical inclusion of potential confounding variables, such as sex drive (see Baer et al, 2015) would have reduced the magnitude of these effects.…”
Section: Discussioncontrasting
confidence: 60%
“…Regardless of how the data were analyzed, the use of pornographic magazines was correlated with self-reported sexual aggression, and stronger linear associations were evident among men with higher predisposed risk of sexual aggression, especially with respect to HM. The total variance in self-reported sexual aggression accounted for by pornographic magazine use was moderate (9-17% in multiple regression analysis; IRRs ranged from 1.31 -1.86) and with respect to the multiple regression results, considerably larger than the reported estimate from a recent meta-analysis concerning "sexualized media" (Burnay et al, 2021). It possible that the analytical inclusion of potential confounding variables, such as sex drive (see Baer et al, 2015) would have reduced the magnitude of these effects.…”
Section: Discussioncontrasting
confidence: 60%
“…Third, the internal consistencies for the two parts of the script measure were just below the accepted threshold of 0.70. Furthermore, we used a broad question to assess frequency of pornography use, which did not distinguish between different types of pornographic content, such as violent vs. nonviolent or mainstream vs. feminist pornography [ 11 , 48 ]. A more fine-grained measure of the type of pornography used would enable future research to examine differential associations with sexual aggression perpetration and victimization [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this line of reasoning, a review found evidence that both sexually explicit material in general, and material depicting rape or physical harm in a sexual context in particular, were linked to attitudes condoning sexual violence and physical dating violence [ 47 ]. Recent meta-analytic reviews found significant links between exposure to pornography, especially violent pornography (defined as depictions of intentional attempts by individuals to inflict extreme physical harm on others, such as rape), and rape myth acceptance and normative beliefs condoning violence [ 48 , 49 ]. Moreover, greater acceptance of sexual aggression and rape myth acceptance have been linked to higher odds of both sexual aggression perpetration and victimization, as shown in recent reviews [ 50 , 51 ].…”
Section: Introductionmentioning
confidence: 99%
“… Just as the potential effect of mass media on social attitudes has been of longstanding interest to communication scholars as a group (Klapper, 1948; Schramm, 1949), so has the potential effect of pornography on sociosexual attitudes been of longstanding interest to sexological communication scholars as a subgroup (Linz & Malamuth, 1993; Wallace & Wehmer, 1971; Zillmann & Bryant, 1982). Despite this, meta-analyses aggregating findings from naturalistic pornography use studies (i.e., studies of actual, rather than experimentally induced, exposure to pornography 1 ), and sociosexual attitudes indicate that cross-sectional survey designs are far more common than longitudinal survey designs (Burnay et al, 2022; Hald et al, 2010). For instance, Tokunaga and colleagues’ (2019) recent meta-analysis of pornography consumption and impersonal sexual attitudes identified 33 cross-sectional surveys but only six longitudinal surveys.…”
Section: Replication Of Wright (2013)mentioning
confidence: 99%